Sharia Economic Legal Contribution of Economic Development in Indonesia: - - Mukharom, Mukharom; Heryanti, B. Rini; Astanti, Dhian Indah; Aravik, Havis (Faculty of Islamic Economics and Business, State Islamic University of Kiai Haji Achmad Siddiq Jember, Indonesia, 2020)
As part of the teachings of Islam, Islamic economic law is important to be taken into account in the formation of national law. Factually Islamic economic law is a living law (the living law) in Indonesian society since the entry of Islam into the archipelago. This research was conducted analytically descriptively, that is a study that described and described the conditions and facts in detail, systematically and thoroughly about the contribution of sharia economic law in economic development in Indonesia and the approach used was juridical empirical, so that the data used in this study namely primary data and secondary data. Primary data is collected by interviewing the subjects determined by the researchers, namely the authorized institutions / agencies, while secondary data is obtained from literature, legislation and related documents. The problem in this study is how the contribution of Islamic economic law to economic development in Indonesia. The results of his research are 1. Islamic economics as a surefire solution to poverty alleviation, this is very appropriate because the poor are not seen as a lazy party, but as a party that does not get access to a better life. Here in lies the difference between the Islamic and conventional economic systems. The Islamic economic system does not aim to accumulate as much wealth as possible. But, how a better life can be achieved together, the meaning is mutual help in the good between those who have excess property against those who need these assets. 2. The efforts to positivate the Islamic economy itself have actually been going on for a long time and this needs to be supported. 3. One of the problems now faced by the Islamic finance industry in Indonesia is the availability of quality human resources. The continued development of the Islamic finance and banking industry is driving the need for quality human resources. Economics is an integral part of Islamic teachings, and therefore Islamic economics will be realized only if Islamic teachings are fully believed and implemented. Islamic economics studies the economic behavior of individuals who are consciously guided by the teachings of Islam, the Koran and the Sunnah in solving the economic problems they face.